PENGARUH PENGGUNAAN MEDIA KAHOOT TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP MUHAMMADIYAH 12 BINJAI - Fitri Lestari; Widya Masitah (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2022)
The problem in this study are the low learning motivation of students in the learning process using kahoot media, the lackof implementation of Islamic religious education learning using kahoot media and what is the effect of using kahoot media on student learning motivation. This study aims to determine the motivation to learn by usin kahoot media, to determine the implementation of Islamic religious education learning by using kahoot media and to determine the effect of using kahoot media on student’s learning motivation. This research was conducted at SMP Muhammadiyah 12 Binjai which is located at JL. K.H A. Dahlan No.4, Kartini, kec. Binjai City, Binjai City, North Sumatera 20713. The population in this study was all class VIII SMP Muhammadiyah 12 Binjai, amounting to 34 people. With a total sampling research sampel, namely the entire population as a sampel. There is a difference in the average value between the class before using the media (48.73529) and the class after using the media (53.06897) it can be seen that the average value in the class before using the media (53.06897>48.73529). then from the t test result obtained from t count t table ie 21,332 > 2,036933. It can be concluded that there is an effect of using kahoot media on student’ learning motivations in Islamic religious education subject at SMP Muhammadiyah 12 Binjai.